Calcium signaling in postsynaptic mitochondria: mechanisms, dynamics, and role in ATP production - Feofilaktova, Tatiana; Kushnireva, Liliia; Segal, Menahem; Korkotian, Eduard (Frontiers in Molecular Neuroscience, 2025)
While the overall ATP level in neurons remains relatively stable, local fluctuations in synaptic compartments - driven by synaptic potentials - necessitate rapid ATP adjustments. The energy supply for synaptic activity in neurons must be under precise homeostatic control: increased ATP consumption in active synapses requires continuous replenishment, whereas in periods of inactivity, excess ATP production may occur. Overproduction of ATP in thousands of individual synapses is metabolically wasteful, while underproduction threatens to disrupt molecular cascades associated with ongoing synaptic bursts, ion homeostasis, protein synthesis, and neural plasticity. Fine-tuned regulation of ATP synthesis must therefore be controlled locally and dynamically, ensuring metabolic efficiency while preventing disruptions in synaptic bursts, ion homeostasis, and neuronal plasticity. This review summarizes the intricate molecular mechanisms through which mitochondria (MT) interact with their postsynaptic environment to maintain energy balance. We examined the fundamental features of mitochondria in conjunction with their unique properties and roles in nervous tissue, highlighting their ability to dynamically adjust energy production based on local demand rather than maintaining a strictly uniform ATP output. The regulation of ATP synthesis may involve mitochondrial transport, fusion, and fission, as well as changes in mitochondrial shape and molecular structure. This review describes the activity of ATP synthase, the mitochondrial calcium uniporter and other signaling cascades in the context of their uneven distribution within mitochondria. Furthermore, we discuss rapid calcium influxes from postsynaptic membranes and the endoplasmic reticulum into mitochondria-associated membranes (MAMs), their buffering mechanisms, and the generation of dynamic responses. We focus on the role of calcium ion (Ca2+) as a precise regulator of ATP production, particularly in mitochondria located near synaptic regions, where it ensures an adequate energy supply for local activity. Overall, we propose potential pathways of interaction between mitochondria and their postsynaptic microdomains. Given that some of the mechanisms discussed remain hypothetical, we emphasize the urgent need for experimental validation to refine understanding of mitochondrial function in synaptic transmission.